Four new species and three new records of helicosporous hyphomycetes from China and their multi-gene phylogenies - Lu, Yong-Zhong; Ma, Jian; Xiao, Xing-Juan; Zhang, Li-Juan; Xiao, Yuan-Pin; Kang, Ji-Chuan (Frontiers in Microbiology, 2022)
Helicosporous hyphomycetes have the potential to produce a variety of bioactive compounds. However, the strain resources of this fungal group are relatively scarce, which limits their further exploitation and utilization. In this study, based on phylogenetic analyses of combined ITS, LSU, RPB2 and TEF1α sequence data and the morphology from 11 isolates, we introduce four new species of helicosporous hyphomycetes, viz. Helicoma wuzhishanense, Helicosporium hainanense, H. viridisporum and Neohelicomyces hainanensis, as well as three new records, viz. Helicoma guttulatum, H. longisporum and Helicosporium sexuale. The detailed morphological comparisons of the four new species that distinguish them are provided.